Brolls over trolls : encouraging positive social media behaviour among young netizens - Heng, Abigail (2015)
Brolls Over Trolls (BOT) is a communications campaign which aims to empower youths aged 18 to 29 to adopt positive social media behaviour amidst a landscape flooded with trolls. It is the first campaign of its kind to create a symbol that encapsulates the anti-thesis of a troll. This report provides the insights behind the team’s extensive formative research, which were instrumental in formulating the campaign’s strategy and tactics. An assessment was then conducted on the campaign’s objectives to evaluate the success of it. Finally, this report will discuss the limitations of the campaign, and explore possibilities of future expansion of the project. This paper also includes original documents, research, collaterals, diagrams and transcripts of conversations in the appendices as further references.